Comparison on Plant Growth, Yield and Quality of Broccoli (Brassica oleracea L. var. italica Plenck) Varieties in Sindhuli and Kailali Districts Of Nepal - Giri, Hom Nath; Lamsal, Ganesh; Upreti, Ramesh (Journal of Agriculture and Forestry University, 2025)
Broccoli (Brassica oleracea L. var. italica Plenck) is a highly valued vegetable in Nepal. Head size and quality of broccoli largely depend on temperature and genetic potentiality. Hence, location specific varietal selection is crucial. Two experiments were conducted to evaluate the growth, yield and postharvest quality of broccoli varieties in Sindhuli and Kailali districts of Nepal during October, 2024 to February, 2025. The experiment was laid out in Randomized Complete Block Design with four replications. The five broccoli varieties studied were Calabrese, Chitwan Local, Centauro, Everest Green and Green Pia. Results revealed that in Sindhuli significantly the maximum plant height (75.27 cm), number of leaves (13.44), earliest head initiation (43.50 days) and maturity (58.5 days) were observed in Calabrese; however, head diameter (19.17 cm) and yield (21 mt/ha) were maximum in Everest Green which was at par with Centauro (19.45 mt/ha). In Kailali, maximum number of leaves (11.7) and leaf area (327.72 cm2) were observed in Chitwan Local; highest plant height, earliest head initiation (41.5 days) and maturity (53.75 days) in Calabrese; maximum head diameter (17 cm) in Green Pia and yield (19 mt/ha) was maximum in Everest Green which was statistically at par with Green Pia and Centauro. TSS, TA% and pH differed in Sindhuli but remained similar in Kailali. Green Pia had the longest shelf life in both the locations. Thus, Everest Green and Centauro in Sindhuli, while any variety among Everest Green, Centauro and Green Pia in Kailali proved to be promising to maximize the yield.